1992
DOI: 10.1128/aem.58.2.496-501.1992
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites formed during anaerobic transformation of toluene and o-xylene and their proposed relationship to the initial steps of toluene mineralization

Abstract: Strain Tl is a facultative bacterium that is capable of anaerobic toluene degradation under denitrifying conditions. While 80% of the carbon from toluene is either oxidized to carbon dioxide or assimilated into cellular carbon, a significant portion of the remainder is transformed into two dead-end metabolites. These metabolites were produced simultaneous to the mineralization of toluene and were identified as benzylsuccinic acid and benzylfumaric acid. Identification was based on comparison of mass spectra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
2
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 14 publications
6
62
2
4
Order By: Relevance
“…Krieger, M. Reinhard and A.M. Spormann, unpublished data). The o-and p-xylene isomers can also be co-metabolized with toluene and converted to dead-end products by some bacterial strains [33,44,47,68]. So far, only one pure culture growing on o-xylene has been obtained [34], and no pure cultures growing on p-xylene have yet been reported.…”
Section: Conclusion/outlookmentioning
confidence: 99%
“…Krieger, M. Reinhard and A.M. Spormann, unpublished data). The o-and p-xylene isomers can also be co-metabolized with toluene and converted to dead-end products by some bacterial strains [33,44,47,68]. So far, only one pure culture growing on o-xylene has been obtained [34], and no pure cultures growing on p-xylene have yet been reported.…”
Section: Conclusion/outlookmentioning
confidence: 99%
“…A few isolates were reported to grow with m-xylene (Dolfing et al, 1990;Fries et al, 1994;Rabus & Widdel, 1995;Harms et al, 1999;Morasch et al, 2004) or o-xylene (Harms et al, 1999;Morasch et al, 2004); no pure culture was described yet degrading p-xylene anaerobically. A few studies showed that the anaerobic degradation of xylene isomers was initiated by addition of fumarate to a methyl moiety (Evans et al, 1992;Beller & Spormann, 1997;Krieger et al, 1999;Morasch et al, 2004;Morasch & Meckenstock, 2005), a reaction catalyzed by the enzyme benzylsuccinate synthase (BSS). The anaerobic degradation of several aliphatic hydrocarbons and alkylated aromatics is initiated by this reaction type (for an overview, see Heider, 2007), and the gene coding for the alpha subunit of BSS, bssA, was found in several sequence types (Winderl et al, 2007), indicating the existence of several isoenzymes of BSS.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas maltophilia SU1 appears more versatile than other pure cultures of organisms that degrade aromatic hydrocarbons in the absence of oxygen. Pseudomonas T1 described by Evans et al [17,19] utilizes only toluene as a growth substrate, but converts o-xylene to a dead end metabolite when toluene is present in the medium [19]. Dolfing et al [5] and Schocher et al [6] studied a number of strains of Pseudomonas that could degrade toluene, and a number of toluene-related compound under denitrifying conditions.…”
Section: Discussionmentioning
confidence: 99%